pH-Responsive Particle-Liquid Aggregates—Electrostatic Formation Kinetics - Ireland, Peter M.; Kido, Kohei; Webber, Grant B.; Fujii, Syuji; Wanless, Erica J. (Frontiers in Chemistry, 2018)
Liquid-particle aggregates were formed electrostatically using pH-responsive poly[2-(diethylamino)ethyl methacrylate] (PDEA)-coated polystyrene particles. This novel non-contact electrostatic method has been used to assess the particle stimulus-responsive wettability in detail. Video footage and fractal analysis were used in conjunction with a two-stage model to characterise the kinetics of transfer of particles to a water droplet surface, and internalisation of particles by the droplet. While no stable liquid marbles were formed, metastable marbles were manufactured, whose duration of stability depended strongly on drop pH. Both transfer and internalisation were markedly faster for droplets at low pH, where the particles were expected to be hydrophilic, than at high pH where they were expected to be hydrophobic. Increasing the driving electrical potential produced greater transfer and internalisation times. Possible reasons for this are discussed.